Pengaruh Kepercayaan, Kemudahan Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada E-commerce Shopee (Studi Pada Mahasiswa Manajemen Universitas Islam Malang Angkatan 2019) - Dewi Sinta; Ronny Malavia Mardani; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to analyze and describe the effect of trust, convenience, and service quality on purchasing decisions at e-commerce shopee (study of management students from the Faculty of Economics and Business class of 2019). The population in this study were 598 undergraduate management students at the Faculty of Economics and Business, Islamic University of Malang, from the Management study program. Then, from this number, 86 samples weretaken using the slovin formula. The variables used in this study are purchasing decision variables (the dependent variable), while the independent variables are trust, convenience, and service quality.The results of this study concluded that partially there is an influence between the variables of trust, convenience, and quality of service on purchasing decisions. Keywords: purchase decision, trust, convenience, service quality